El cómic como estrategia didáctica en el aprendizaje significativo de Biología Vegetal con los estudiantes de tercer semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Remache Cuji, Leonor Esthela (2024)
The main objective of this research study was to focus on complex subjects taught at the Universidad Nacional de Chimborazo such as Plant Biology which requires the student to read books and magazines to understand the contents, this makes the student feel disinterested in acquiring new knowledge and see it as a very difficult subject to learn. In such virtue the comic is an efficient didactic strategy to reach towards the significant learning, it stands out for its characters, vignettes, backgrounds, colors and texts that make an ideal complement to facilitate the comprehension of the knowledge. Therefore, the objective was to propose the ‘Comic “Biodiversion” as a didactic strategy in the significant learning of Plant Biology’; the methodology applied was with quantitative approach, non-experimental design, bibliographic type, field, descriptive level, inductive method, survey technique, questionnaire instrument. Thirty-two third-semester students of the Pedagogy of Experimental Sciences, Chemistry and Biology in the academic period 2023-2s participated in this study. According to the results obtained, the degree of interest, motivation and acceptance of this strategy was known, since 81% of the respondents expressed that it was novel and very easy to use. Therefore, it was concluded that the comic as a didactic strategy is an orientation guide for obtaining significant results, helping to optimize the learning process, breaking paradigms and seeking a new way of constructing lasting and long-term knowledge.